RELEVANSI KRITIK SASTRA MARXIS PADA NOVEL BUI KARYA ALAN TH SEBAGAI BAHAN AJAR DI SMA ISLAM TA’ALLUMUL HUDA BUMIAYU - Ifadakh, Amanda Qori; Wakhyudi, Yukhsan (Universitas Peradaban, 2024)
This study aims to analyze and describe the intrinsic elements, Marxist literary criticism, and its relevance as teaching materials at SMA Islam Ta'allumul Huda Bumiayu. The approach used is Marxist literary criticism. The research method used in this study is qualitative. Data collection techniques used are observation, interviews, and documentation. The results of the study indicate that four forms of Marxist literary criticism were found, which include social structures included in the socio-economic aspect, ruling class ideology and cultural hegemony included in the aspects of ideology and cultural hegemony, class consciousness and revolutionary potential and economic and social development included in the aspect of historical materialism. It is indicated by the existence of a power structure, social class, and the struggle of the upper and lower classes experienced by the characters in the novel. The relevance of the analysis of Marxist literary criticism in the BUI novel by Alan TH as teaching materials at SMA Islam Ta'allumul Huda Bumiayu is found in the socio-economic aspect, ideology and cultural hegemony, as well as class consciousness and revolutionary change relevant to Core Competency 11.4 with the achievement of the indicator of writing criticism on the novel. Keywords: novel, marxist literary criticism, teaching materials